2010
DOI: 10.1097/nmd.0b013e3181f49ea3
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Interventions for Severe Mental Illness

Abstract: Mobile devices can be used to deliver psychosocial interventions, yet there is little prior application in severe mental illness. We provide the rationale, design, and preliminary data from three ongoing clinical trials of mobile interventions developed for bipolar disorder or schizophrenia. Project 1 used a personal digital assistant to prompt engagement in personalized self-management behaviors based on real-time data. Project 2 employed experience sampling via text messages to facilitate case management. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(141 citation statements)
references
References 36 publications
6
130
1
1
Order By: Relevance
“…In terms of study limitations, first, as previously mentioned, our findings regarding higher anticipatory pleasure ratings may be due the social interactions with the research caller (cell phone calls, for example, are known to increase participant involvement in treatment) (e.g., Depp et al, 2010; Ehrenreich, Righter, Rocke, Dixon, & Himelhoch, 2011). If this mechanism is contributing to enhanced anticipatory pleasure in people with schizophrenia, it may represent an important therapeutic tool that can be explicitly harnessed.…”
Section: Discussionmentioning
confidence: 90%
“…In terms of study limitations, first, as previously mentioned, our findings regarding higher anticipatory pleasure ratings may be due the social interactions with the research caller (cell phone calls, for example, are known to increase participant involvement in treatment) (e.g., Depp et al, 2010; Ehrenreich, Righter, Rocke, Dixon, & Himelhoch, 2011). If this mechanism is contributing to enhanced anticipatory pleasure in people with schizophrenia, it may represent an important therapeutic tool that can be explicitly harnessed.…”
Section: Discussionmentioning
confidence: 90%
“…There are a number of compelling arguments for AA as an intervention platform (Clough & Casey 2011, Cohn et al 2011, Depp et al 2010, Ebner-Priemer & Trull 2009, Wichers et al 2011). First, for decades, clinicians have struggled with the challenge to translate principles and strategies learned in the clinician’s office to the real world of the patients.…”
Section: The Use Of Ambulatory Assessment In Clinical Psychologymentioning
confidence: 99%
“…Kimhy & Corcoran (2008) presented a case report of using AA as a treatment adjunct to improve homework completion and overcome treatment barriers associated with negative symptoms with a female patient at high risk for psychosis. Finally, Depp et al (2010) recently reported on a pilot study where outpatients with bipolar disorder received a preselected self-management strategy reminder after signaling to the PDA that they were experiencing an exacerbation in symptoms or an episode trigger.…”
Section: The Use Of Ambulatory Assessment In Clinical Psychologymentioning
confidence: 99%
“…In this trial the intervention group is being compared to a parallel group using smartphones not capable of collecting objective data as well as to a control group using the smartphone just for communicative purposes (Faurholt-Jepsen, 2014). Depp et al (2010) designed a mood intervention system using Personal Digital Assistant (PDA). Personalized Real-Time Intervention for Stabilizing Mood (PRISM) consisted of an ecological intervention intended to provide self-monitoring of mood states and of an Early Warning Signs (EWS) design to deliver a real time specific and tailored psychoeducational advices for an eventual reduction of mood symptoms.…”
Section: Interventions Delivered By Mobile Technologiesmentioning
confidence: 99%